2022
DOI: 10.13189/saj.2022.100221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the Physical Condition of Football Extracurricular Participants before and during the COVID-19 Pandemic

Abstract: Background: One of the most popular extracurricular activities at school is football. However, extracurricular activities have been temporarily suspended due to the COVID-19 outbreak, which on the other hand will affect students' physical abilities. The purpose of this study was to evaluate the physical condition of students which included speed, endurance, agility, before and during the COVID-19 pandemic. The participants were 15 male students aged 14-15 years with a weight of 51-71± kg and a height of 157-17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The authors utilised a quantitative descriptive research method with a survey approach to generate conclusions from this research (Akhiruyanto et al, 2022;Hafidz et al, 2021). Purposive sampling was utilised in this study, which found a sample of 89 participants who met the criterion for flat feet, aged 15-44 years, male and female.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors utilised a quantitative descriptive research method with a survey approach to generate conclusions from this research (Akhiruyanto et al, 2022;Hafidz et al, 2021). Purposive sampling was utilised in this study, which found a sample of 89 participants who met the criterion for flat feet, aged 15-44 years, male and female.…”
Section: Methodsmentioning
confidence: 99%
“…The instruments in this study were wet footprint tests, stature meter weight scales, and questionnaire sheets (Antara et al, 2017). The data analysis technique used percentage analysis with the formula P=F/N 100%, P=percentage sought, F=frequency, N=number of respondents, data analysis was assisted using the Excel application (Akhiruyanto et al, 2022;Simanjuntak et al, 2022;Yudhistira et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…The coaching system is the main program for producing quality athletes (Akhiruyanto et al, 2022;Hidayati et al, 2022;Yudhistira et al, 2021a;Yudhistira et al, 2021b). Discussions regarding the coaching system will embrace training programs, organizational structures, and evaluation methods.…”
Section: Mahameru Club Taekwondo Athlete Training In Sukoharjo Regencymentioning
confidence: 99%
“…Soccer has been played by over 260 million people, both amateurs and professionals [1]. Soccer's popularity is growing by the day, which naturally motivates players to aim for higher goals [2] [28]. However, accomplishing these goals is not simple.…”
Section: Introductionmentioning
confidence: 99%